2007
DOI: 10.1136/ard.2007.073445
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of early response to methotrexate therapy predicts long-term outcome of patients with juvenile idiopathic arthritis

Abstract: Our results show that the achievement of an ACR Pediatric 70 response at 6 months after start of MTX therapy predicts a more favorable long-term outcome of patients with JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 23 publications
(20 reference statements)
3
31
0
Order By: Relevance
“…A recent study also demonstrated that an ACR Pedi 70 criteria response to methotrexate after 6 months of therapy was associated with improved outcomes, including lower AJC and inactive disease after 5 years, compared with those with lower responses or nonresponders (17). The authors concluded that the early disease course and response to treatment may be stronger predictors of long-term outcome than disease characteristics at onset (17). In patients with systemic JIA, the need for corticosteroids at 6 months after diagnosis is also a predictor of poor functional outcome (33).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A recent study also demonstrated that an ACR Pedi 70 criteria response to methotrexate after 6 months of therapy was associated with improved outcomes, including lower AJC and inactive disease after 5 years, compared with those with lower responses or nonresponders (17). The authors concluded that the early disease course and response to treatment may be stronger predictors of long-term outcome than disease characteristics at onset (17). In patients with systemic JIA, the need for corticosteroids at 6 months after diagnosis is also a predictor of poor functional outcome (33).…”
Section: Discussionmentioning
confidence: 95%
“…However, to put our results in perspective, in 2 recent clinical trials, 44% and 33% of patients with a severe polyarticular disease course who had failed treatment with methotrexate achieved an ACR Pedi 70 criteria response after 7 and 12 months, respectively, with etanercept, and in another trial, 52% reached this response after 1 year of infliximab treatment (21,22,28). The ACR Pedi 70 criteria response rate 6 months after starting methotrexate was 26% in a study of patients with polyarthritis, systemic arthritis, and extended oligoarthritis (17). In our study, 55% of patients with RF-negative polyarthritis achieved an ACR Pedi 70 criteria response, suggesting a good shortterm outcome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In polyarticular disease, arthritis often remains active for longer periods than it does in persistent oligoarthritis,1 3 4 and patients may thus have disease of greater severity and higher risk prolonged 1 3–6. In recent studies, an early response to methotrexate at 6 months predicted better long-term outcome,7 and achieving inactive disease at least once within 5 years from onset also predicted less joint damage 8. Efforts to establish early effective therapies for polyarticular JIA should therefore be strengthened.…”
mentioning
confidence: 99%
“…As expected, there was a higher prevalence of women in both cohorts. Disease duration has been recently reported as linked with MTX response14: the median time of disease duration prior to starting MTX in these two cohorts was around 1 year.…”
Section: Resultsmentioning
confidence: 79%